A plan for a city home ground - Gilbert, Eva May (Rickman) (My University, 1905)
Introduction: The art of gardening is eminently one of the finest of arts for by skillful application of the principles here set forth we may form tasty and impressive pictures from those plants and trees which otherwise, might appear uncouth and out of place. The first requisite in carrying out an idea for the home grounds is to make a definite, written plan so explicit in detail that to eradicate any portion of it would mean to destroy the desired effect and make a new plan a necessity. In this work we should consider the appearance of the landscape the entire year and not simply the summer months. For the improvement of the winter effect I think it impossible to say too much stress upon the desirability of the ever greens. They may be used in very many locations with impunity due to the marked variety in color, size and form. The adaptability to climate and soil varies widely with the different species. As a class they are symmetrical and slow of growth. Very handsome effects may be produced by clumping the evergreens and placing snowballs in the fore growing. The contrast makes this arrangement very beautiful. Among the other trees to be mentioned for winter effects are Quercus Palustris and Quercus Imbricaria because of the leaves being retained during the winter months.
Citation: Gilbert, Eva May (Rickman). A plan for a city home ground. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Small spring Flowers; Quercus Palustris; Picea Pungens; Theses; Manuscripts (documents)